2022
DOI: 10.3390/cells11030444
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem Findings of Inflammatory Cells and the Association of 4-Hydroxynonenal with Systemic Vascular and Oxidative Stress in Lethal COVID-19

Abstract: A recent comparison of clinical and inflammatory parameters, together with biomarkers of oxidative stress, in patients who died from aggressive COVID-19 and survivors suggested that the lipid peroxidation product 4-hydroxynonenal (4-HNE) might be detrimental in lethal SARS-CoV-2 infection. The current study further explores the involvement of inflammatory cells, systemic vascular stress, and 4-HNE in lethal COVID-19 using specific immunohistochemical analyses of the inflammatory cells within the vital organs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 55 publications
3
26
0
Order By: Relevance
“…As demonstrated by the analysis conducted so far, "COVID-19 Is Not Comparable to H1N1 Influenza" [56] (Table 2, Ref. [1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][26][27][28][31][32][33][34][35][36][37][38][39][40][41][42][47][48][49][50][51][52][53][54][55]57]) and histopathological findings play a key role in understanding the pathophysiological mechanisms of diseases and, thus possible therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated by the analysis conducted so far, "COVID-19 Is Not Comparable to H1N1 Influenza" [56] (Table 2, Ref. [1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][26][27][28][31][32][33][34][35][36][37][38][39][40][41][42][47][48][49][50][51][52][53][54][55]57]) and histopathological findings play a key role in understanding the pathophysiological mechanisms of diseases and, thus possible therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study on post-mortem preparations would seem to confirm the role of oxidative stress in the pathogenesis of lethal forms of COVID-19, demonstrated by an abundant immunohistochemical expression of the lipid peroxidation product: 4-hydroxynonenal (4-HNE). The origin of 4-HNE would be vascular stress similar to sepsis and the organs most affected were the lungs with diffuse alveolar damage and the brain with edema and reactive astrocytosis [57]. A recent study attempted to define a unifying theory of the two souls of SARS-CoV-2 infection [65].…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, Nrf2 functions in the cytoplasm in the form of a complex with its inhibitor, the protein Keap1, which directs Nrf2 to ubiquitination-dependent degradation [30]. On the other hand, under oxidative conditions resulting from viral replication, an indicator of which can be observed, an increased level of the lipid peroxidation product -4HNE in the plasma of the same patients with COVID-19 [31] may lead to modifications, by ROS or electrophilic compounds, of the critical sulfhydryl groups of the cysteine of Keap1, the consequence of which is the dissociation of the Nrf2-Keap1 complex and the migration of Nrf2 to the nucleus, where it binds to a DNA sequence known as an antioxidant response element (ARE), in the promoter regions of target genes coding mainly antioxidant enzymes [32], thus increasing the transcription of these genes. The Nrf2 gene also contains the ARE sequence in its promoter [33], enhancing its expression in the positive feedback loop.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one of the inhibitors of the NFκB-IκB complex is major bioactive product of PUFA peroxidation 4-HNE, the level of which increases under oxidative stress [48,49] and was found to be associated with systemic vascular stress in COVID-19 patients, in particular in those who passed away [31,51]. However, it is known that NFκB is essential for maintaining immune homeostasis and preventing autoimmunity caused by COVID-19 [46].…”
Section: Discussionmentioning
confidence: 99%
“…Not only that, the levels of pulmonary 4-HNE were upregulated in patients with COPD (18). In addition, the autopsy report revealed that 4-HNE is more highly expressed in the lungs and kidneys of patients with COVID-19 (27,28).…”
Section: The Predictive Powers For Severity and Deathmentioning
confidence: 93%